APPLICATION OF GROUP GUIDANCE SERVICES WITH COGNITIVE DEFUSION TECHNIQUES IN INCREASING STUDENT CONFIDENCE AT MTS AISYIYAH NORTH SUMATERA - Sukma Permata Sari; Abdul Aziz Rusman (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2023)
Self-development is always related to self-confidence. Self-confidence is important because it influences individual success. The purpose of this study was to determine the effectiveness of the application of group guidance services with cognitive defusion techniques to increase student confidence. The research design used is Quasy Experiment with pre-post-test control group design. In this design, the experimental group received treatment and the control group did not receive treatment. The sample was taken 30 students and then divided into two groups, namely 15 students into the experimental group and 15 other students into the control group. Data collection was taken through a structured questionnaire given to students to measure the level of self-confidence. The instrument applied is the self-confidence scale. Data were analyzed using Microsoft Excel software and SPSS Version 25. The analysis applied hypothesis testing (t test). The results of the analysis obtained information, t P <0.05, namely (0.001 <0.05) the significance value is less than 0.05 so that the hypothesis is accepted. This indicates that group guidance services with cognitive defusion techniques are effective for increasing students' confidence levels.